2015
DOI: 10.1002/pmic.201400434
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of Giardia duodenalis assemblage A: A baseline for host, assemblage, and isolate variation

Abstract: Giardia duodenalis is a gastrointestinal protozoan parasite of vertebrates and is a species complex comprised of eight assemblages, with the zoonotic assemblage A one of two subtypes infective for humans. With increasing genomic and transcriptomic data publicly available through the centralized giardiaDB.org, we have quantitatively analyzed the proteomes of eight G. duodenalis assemblage A strains (seven A1 and one A2) to provide a proteomic baseline to complement the available data. A nonredundant total of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…S2). This represents more than a quarter of the open reading frames predicted by the respective genomes in this single life cycle stage under this steady state set of in vitro culture conditions and compares favourably with other recent proteomic analyses of Giardia [17, 18]. Lists of proteins detected in only 1 of the 2 assemblages are provided (Additional file 2: Tables S1 and S2).…”
Section: Analysessupporting
confidence: 72%
“…S2). This represents more than a quarter of the open reading frames predicted by the respective genomes in this single life cycle stage under this steady state set of in vitro culture conditions and compares favourably with other recent proteomic analyses of Giardia [17, 18]. Lists of proteins detected in only 1 of the 2 assemblages are provided (Additional file 2: Tables S1 and S2).…”
Section: Analysessupporting
confidence: 72%
“…In total, there were 2 large functional clusters that varied between strains and life cycle stages; 'VSP/Furin-like/EGFlike' and 'ankyrin-repeat'. Both these clusters feature proteins from the Giardia variable genome already implicated in inter-and intra-assemblage variation [23,49,51]. These data reinforce the hypothesis that the diversity seen in such families at the genome level translates to crucial differences at the level of the expressed proteome between strains at both life cycle stages.…”
Section: Strain-specific Adaptations During Encystationsupporting
confidence: 67%
“…Intra-assemblage variation within G. duodenalis is yet to be comprehensively analysed since genomes have become available, although it has been shown that Giardia-specific gene families of the variable genome differ between assemblages [49,50]. Protein expression of VSP variants also varies between cultured trophozoites from multiple strains of the same subassemblage [51]. Between the 488 and the 688 reproducibly identified proteins in H-106 and B-2041 cysts, 373 proteins were common, which corresponds to 76.4% of cyst proteins from H-106 and 54.2% of proteins from B-2041 cysts (Fig.…”
Section: Strain-specific Adaptations During Encystationmentioning
confidence: 97%
See 2 more Smart Citations